Revalidation of the Federal PTRA: Testing the PTRA for Predictive Biases - Cohen, Thomas H. (Criminal justice and behavior, 2018)
The pretrial risk assessment instrument (PTRA) was developed for use in the U.S. federal pretrial system. Specifically, this instrument was constructed to help officers assess the likelihood that defendants will commit pretrial violations including being rearrested for new crimes, missing court appearances, or being revoked while on pretrial release. This research evaluates the PTRA’s capacity to predict pretrial violations on 85,369 defendants with officer-completed PTRA assessments. Bivariate and multivariate models were estimated by race, ethnicity, and sex. Results show that the PTRA performs well at predicting pretrial violations as the area under the receiver operating characteristic curve ranged from 0.65 to 0.73 depending upon the subsamples and outcomes being predicted. Moreover, the PTRA predicted new criminal arrest activity equally well for non-Hispanic Whites and Blacks, while for Hispanics and females, findings show the instrument validly predicting rearrest activity, with some evidence of overprediction depending upon the outcome being examined.